(untitled) (Journal of Philosophy Culture and Political Science, 2018)
The article reviews the philosophy of Asan Kaygi and the concept of «Zheruyik». Role of Asan Kaygi in the history of Kazakh philosophy still studying in modern terms. Every age has own problems, superficial thinkers, and ruling khans. They live in an atmosphere of anticipation and predictability of those difficulties. It is determined by the fact that Asan Kaygi’s place is differ from as it is supposed to predict the difficulty of the future. We also can see other manifestations of the philosophy of the Change and the spiritual support of the ideas of Asan Kaygi. The fate of Bukhar Zhyrau is similar to the life of Asan Kaygi. It is noted that Bukhar Zhyrau plays a key role in the history of Kazakhstan. Analysis of the meaning and significance of the notion of time and analyzed his role in the Kazakh philosophy. Key words: Asan Kaygy, Kily zamy, Kazakh philosophy, Zheruik, Mangilik El. Kazakh Country.